Effect of Organic Surface Concentration on CO2-Wettability of Reservoir Rock - Ali, Muhammad (Curtin University, 2018)
This study involves the effect of organic acids on wettability for CO2 trapping capacities in deep saline aquifers and depleted hydrocarbon reservoirs. The minerals chosen for this study included calcite and quartz, the organic acids chosen were hexanoic acid (C6), lauric acid (C12), stearic acid (C18), and lignoceric acid (C24). The results showed that the mineral/ CO2/brine contact angle increased in the presence of organic acids, implying that rock is more CO2-wet, hence less trapping capacity.